6-Minute Push Test in Youth Who Have Spina Bifida and Who Self-Propel a Wheelchair: Reliability and Physiologic Response. Issue 10 (14th July 2020) - Damen, Karlijn M S; Takken, Tim; de Groot, Janke F; Backx, Frank J G; Radder, Bob; Roos, Irene C P M; Bloemen, Manon A T
Abstract: Objective: Despite the common occurrence of lower levels of physical activity and physical fitness in youth with spina bifida (SB) who use a wheelchair, there are very few tests available to measure and assess these levels. The purpose of this study was to determine reliability and the physiologic response of the 6-minute push test (6MPT) in youth with SB who self-propel a wheelchair. Methods: In this reliability and observational study, a sample of 53 youth with SB (5–19 years old; mean age = 13 years 7 months; 32 boys and 21 girls) who used a wheelchair performed 2 exercise tests: the 6MPT and shuttle ride test. Heart rate, minute ventilation, respiratory exchange ratio, and oxygen consumption were measured using a calibrated mobile gas analysis system and a heart rate monitor. For reliability, intraclass correlation coefficients (ICCs), SE of measurement, smallest detectable change for total covered distance, minute work, and heart rate were calculated. Physiologic response during the 6MPT was expressed as percentage of maximal values achieved during the shuttle ride test. Results: The ICCs for total distance and minute work were excellent (0.95 and 0.97, respectively), and the ICC for heart rate was good (0.81). The physiologic response during the 6MPT was 85% to 89% of maximal values, except for minute ventilation (70.6%). Conclusions: For most youth with SB who use a wheelchair for mobility or sports participation, the 6MPT is a reliable, functional performance test on a vigorous level of exercise. Impact: This is the first study to investigate physiologic response during the 6MPT in youth (with SB) who are wheelchair using. Clinicians can use the 6MPT to evaluate functional performance and help design effective exercise programs for youth with SB who are wheelchair using.